2004
DOI: 10.1074/jbc.m308522200
|View full text |Cite
|
Sign up to set email alerts
|

The Peroxisome Proliferator-activated Receptor γ Regulates Expression of the Perilipin Gene in Adipocytes

Abstract: Reporter assays using the ؊2.0-kb promoter revealed that this region contains a functional PPAR␥-responsive element. Gel mobility shift and chromatin immunoprecipitation assays showed that endogenous PPAR␥ protein binds to the perilipin promoter. PPAR␥2, an isoform exclusively expressed in adipocytes, was found to be the most potent regulator from among the PPAR family members including PPAR␣ and PPAR␥1. These results make evident the fact that perilipin gene expression in differentiating adipocytes is crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(137 citation statements)
references
References 33 publications
(41 reference statements)
6
126
0
5
Order By: Relevance
“…Many adipocyte-specific genes, including the perilipin gene (38,39,46,47), are regulated by PPAR␥, a master regulator of adipogenesis (37). Accordingly, we were interested in whether the CGI-58 gene is also regulated by PPAR␥.…”
Section: Discussionmentioning
confidence: 99%
“…Many adipocyte-specific genes, including the perilipin gene (38,39,46,47), are regulated by PPAR␥, a master regulator of adipogenesis (37). Accordingly, we were interested in whether the CGI-58 gene is also regulated by PPAR␥.…”
Section: Discussionmentioning
confidence: 99%
“…This action of fatty acids could be mediated through the nuclear receptors PPAR␥ because it has been shown that the promoter of the perilipin gene contains functional PPAR-responsive elements and that PPAR␥ agonists stimulate in adipocytes the expression of perilipin. 28,29 Perilipin opposes in adipocytes in the basal state the hydrolysis of TGs by HSL. 19 On stimulation of lipolysis by ␤-adrenergic agonists, perilipin is phosphorylated by the protein kinase PKA and allows phosphorylated HSL to access lipid droplets and hydrolyze TGs.…”
Section: Discussionmentioning
confidence: 99%
“…When fed a high fat diet, perilipin null mice are resistant to dietinduced obesity. PPAR␥ agonists are reported to stimulate perilipin gene expression in adipocytes (39). Reporter assays reveal that the 5Ј-flanking region of the gene contains a functional PPAR␥-responsive element (40).…”
Section: Conclusion -T Z D S R E D U C Ementioning
confidence: 99%